(untitled) (Fiep Bulletin - online, 2014)
The effects of physical exercises in the prevention, promotion and rehabilitation of health have been described by the scientific literature as an important factor in the promotion of people’s life quality. The cognitive, behavioral and somatic techniques - TCCS, can also be a factor for the quality of human life. This study had as objective to verify the effect of a program of physical exercises and of TCCS about the intensity of university students’ pain. Two groups took part in the investigation: a control group, with sixteen students and the other, an experimental group, with seventeen students. The groups were chosen randomly among the several divisions of students’ of the university courses. The program consisted of two weekly sessions, with fifteen minutes each, of which ten minutes were of articulate mobility exercises and five minutes of TCCS, in a period of two months time, making a total of sixteen sessions. As an instrument of the research a questionnaire was applied in both groups in order to verify the existent relationships. This questionnaire evaluated the frequency and the intensity of pain before and after the application of the program. For the experimental group, through the results of the non-parametric test of Wilcoxon, it was verified that significant difference exists among the results obtained in the moments before and after the test in the variable Intensity of Pain. It is observed that, in the experimental group, the intensity of pain in the period after the program was inferior, in other words, there was a significant reduction in the intensity of pain after the accomplishment of the program. (Z=-2,695;p=0,007). The final results suggest a relationship between the program and the decrease of the pain intensity in the experimental group.